AB0555 Anca vasculitis and classic cardiovascular risk factors: coincidence or causality?. (15th June 2017) - Busca, C; Ríos, JJ; Robles, Ά; Noblejas, A; Martínez, E; Soto, C; Vives, I; Troncoso, JA; Bailόn, L; Arnalich, F
Abstract : Background: Unlike other systemic autoimmune diseases (rheumatoid arthritis or systemic lupus erythematosus), the mechanisms involved and the association between ANCA vasculitis with cardiovascular risk factors (CVRF) or cardiovascular events (CVE) are unknown. There may be a phenomenon of "early" atherosclerosis that contributes to an increased cardiovascular risk. This process would not be explained only by the co-existence of the classics CVRF. Objectives: We reviewed the prevalence of classical CVRF and CVE in a cohort of patients diagnosed with ANCA vasculitis. We analyzed whether the appearance of these factors was prior to or subsequent to the diagnosis of the disease or during its evolution. Methods: A descriptive cross-sectional analysis of the classic CVRF and CVE was analyzed in a cohort of patients with ANCA positive vasculitis in follow-up in the Autoimmune Diseases Division of a Spanish hospital. The main demographic characteristics, type of vasculitis and the presence of arterial hypertension, type 2 diabetes mellitus (T2DM), dyslipemia, smoking and obesity were reviewed. Likewise we analyzed CVE (heart failure -HF-, acute coronary syndrome -ACS-, stroke or transient ischemic attack -TIA- and peripheral arteriopathy –PA-) and if each factor was presented at the diagnosis of the disease or they appeared during the evolution after starting immunosuppressive treatment. Results: A total of 35 patients were studied: 21 women (60%) and the average age was 53 years old. A number of 15 were microscopic polyangiitis, 9 granulomatosis with polyangiitis and 11 allergic granulomatous angiitis. Twenty one patients presented hypertension, 9 of them (42.9%) developed it after the diagnosis of vasculitis. From 7 patients with diabetes mellitus, 5 of them were before diagnosed with vasculitis. Nineteen presented dyslipemia and 9 of them (47.4%) presented lipid alteration during the evolution of vasculitis. Overweight/obesity was evident in 4 of the 11 cases after the diagnosis of vasculitis. Only 5 patients did not have a cardiovascular event. ACS was observed in 3 patients, HF in 2 and PA in 1 patient. There were no cases of TIA or ischemic stroke. Four of them had dyslipidemia (3 after diagnosis of vasculitis) (p=0.18) and 3 had hypertension (2 after diagnosis of vasculitis, p=0.66). Three patients were overweight or obese (p=0.3) and two had T2DM (p=0.2), both of them appeared after the diagnosis. Previous history of smoking was observed in 4 of the 5 patients (p=0.06). In 3 patients (71.4%) the cardiovascular event was recorded prior to vasculitis diagnosis and only in 2 cases it occurred during the evolution. Conclusions: This study shows that a high percentage of patients with ANCA vasculitis also presents some type of classic CVRF despite of CVE were not elevated. The diagnosis and treatment of ANCA-positive vasculitis did not statiscally correlate with a greater number of CVE, therefore it would be necessary to carry out studies with a larger number of patients in order to establish conclusions. It is not well defined that weight may have these factors in the prognosis of patients with ANCA vasculitis. These data suggest the need to maintain a close monitoring and therapeutic approach of classic CVRF in this relatively young group of patients. References: Cohen Tervaert JW. Best Pract Res Clin Rheumatol. 2013 Feb;27 (1):33–44. Disclosure of Interest: None declared